Identification of the regulatory phosphorylation sites in pp42/mitogen-activated protein kinase (MAP kinase). - Payne, D M (1991)
Mitogen-activated protein kinase (MAP kinase) is a 42 kd serine/threonine protein kinase whose enzymatic activity requires phosphorylation of both tyrosyl and threonyl residues. As a step in elucidating the mechanism(s) for activation of this enzyme, we have determined the sites of regulatory phosphorylation. Following proteolytic digestion of 32P-labeled pp42/MAP kinase with trypsin, only a single phosphopeptide was detected by two-dimensional peptide mapping, and this peptide contained both phosphotyrosine and phosphothreonine. The amino acid sequence of the peptide, including the phosphorylation sites, was determined using a combination of Fourier transform mass spectrometry and collision-activated dissociation tandem mass spectrometry with electrospray ionization. The sequence for the pp42/MAP kinase tryptic phosphopeptide is similar (but not identical) to a sequence present in the ERK1- and KSS1-encoded kinases. The two phosphorylation sites are separated by only a single residue. The regulation of activity by dual phosphorylations at closely spaced threonyl and tyrosyl residues has a functional correlate in p34cdc2, and may be characteristic of a family of protein kinases regulating cell cycle transitions.